2011
DOI: 10.1007/s10337-010-1890-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of T-2 and HT-2 Toxins in Traditional Chinese Medicine Marketed in China by LC–ELSD after Sample Clean-Up by Two Solid-Phase Extractions

Abstract: LC-ELSD has been applied for the determination of T-2 and HT-2 toxins in Traditional Chinese Medicine (TCM) marketed in China. For sample preparation, two clean-up procedures were developed using Florisil and MycoSep227 for solid-phase extraction. Limits of detection (10 ng g -1 ) as well as recoveries are described. A total of 138 samples of 46 commercially available TCM samples was analyzed; only one sample was determined to contain T-2 at a level of 64.0 ng g -1 , and positive results were further confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…T-2 toxin is the most toxic type A trichothecene mycotoxin, and can be detected in grain, animal feed, drinking water, and Chinese herbs [ 2 , 3 , 4 , 5 ]. It also can accumulate in the body of animals and humans by feed or food consumption and cause potential health risks [ 2 , 3 , 4 , 5 ]. A recent study showed that T-2 toxin was detected in 2.3% of human urine samples from 260 rural residents of Nanjing City, China [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T-2 toxin is the most toxic type A trichothecene mycotoxin, and can be detected in grain, animal feed, drinking water, and Chinese herbs [ 2 , 3 , 4 , 5 ]. It also can accumulate in the body of animals and humans by feed or food consumption and cause potential health risks [ 2 , 3 , 4 , 5 ]. A recent study showed that T-2 toxin was detected in 2.3% of human urine samples from 260 rural residents of Nanjing City, China [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that T-2 toxin was detected in corn, wheat, barley, and rice crops in the field, during storage, or in drinking water in several provinces of China (e.g., Qinghai and Sichuan Provinces) [ 3 ]. T-2 toxin was detected in Chinese herbs [ 4 , 5 ]. It has been demonstrated that T-2 toxin can be easily absorbed through gut and pulmonary mucosa and the skin system, damaging multiple organs of animals and humans, including skin, kidneys, liver, brain, heart, spleen, the hematopoietic system, the lymphoid system, gastrointestinal bone marrow, and the reproductive system [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data obtained for mycotoxins in liquorice roots were mostly reported for food products, and analyses of liquorice products as herbal medicines are scarce. Tan et al [41] in a survey of 138 TCMs from the Chinese market for Fusarium toxins T-2 and HT-2 found that only one sample of barley malt (Hordeum vulgare) was positive for T-2, while all three samples of liquorice were negative (Table 2). However, other research conducted for fumonisins showed their lack in products [42,43] or in the case of Roy et al's work [44], a low level.…”
Section: Glycyrrhiza Glabra (Liquorice)mentioning
confidence: 99%
“…In fact, a number of methods exist for the analysis of mycotoxins. Most methods are based on high-performance liquid chromatography-ultraviolet light (HPLC-UV) [ 16 , 17 ], high-performance liquid chromatography-fluorescence detection (HPLC-FLD) [ 18 , 19 , 20 ], and liquid chromatography-evaporative light scattering detector (LC-ELSD) [ 21 , 22 ]. However, these methods have several drawbacks, particularly at low residual levels, causing false-positives [ 23 ].…”
Section: Introductionmentioning
confidence: 99%